2020
DOI: 10.31234/osf.io/9fdu2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immediate psychological responses during the initial period of the COVID-19 pandemic among Bangladeshi medical students

Abstract: Background: The most recent global pandemic of COVID-19 has been creating multidimensional damages, including a detrimental impact on the mental health status of individuals. Medical students, a vulnerable cross-section of the population, may have perceived a myriad of psychological stressors during this crisis in the background of their prevailing stressful academic pressure and preexisting higher psychological and mental health issue.Objective: To determine the prevalence of anxiety and depressive symptoms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…They have shown 33.7% in anxiety symptom, 57.9% in depressive symptom 59.7% in mild to too severe level of stress. Hasan et al (2020) have extracted results from their study on mental health & well-being among home quarantined Bangladeshi students. It is shown that 28.5 % of the respondents had stress, 33.3% anxiety, 46.92% depression from mild to too severe, and according to DASS 21 and 69.31% had event-specific distress from mild to severe in terms of severity according to IES.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They have shown 33.7% in anxiety symptom, 57.9% in depressive symptom 59.7% in mild to too severe level of stress. Hasan et al (2020) have extracted results from their study on mental health & well-being among home quarantined Bangladeshi students. It is shown that 28.5 % of the respondents had stress, 33.3% anxiety, 46.92% depression from mild to too severe, and according to DASS 21 and 69.31% had event-specific distress from mild to severe in terms of severity according to IES.…”
Section: Literature Reviewmentioning
confidence: 99%